Training on the Utilization of ChatGPT to Support Academic Writing of PTI Students - Safitri, Baiq Rina Amalia; Putrayadi, Wirawan; Fuaddunazmi, M (Sasambo: Jurnal Abdimas (Journal of Community Service), 2026)
This study focuses on the utilization of ChatGPT to support academic writing among students of the Information Technology Education (ITE) program at Universitas Pendidikan Mandalika (UNDIKMA). A training program was conducted from May 15 to May 29, 2024, with 23 second-semester students participating. The program aimed to equip students with the skills to effectively use ChatGPT for generating ideas, drafting outlines, summarizing information, and writing academic texts. Results from the training indicated that all participants successfully created ChatGPT accounts and demonstrated active engagement throughout the sessions. The survey results, with an average of 62.82%, showed that while students gained a strong technical understanding of ChatGPT, their ability to use it for academic writing tasks was still in the early stages, requiring further practice and mentorship. The study found that while ChatGPT can significantly enhance academic writing skills by providing structural guidance and generating ideas, students still need ongoing support to fully integrate AI technology into their academic workflows. These findings emphasize the need for structured training and further integration of ChatGPT in higher education to foster critical thinking, writing, and digital literacy skills.